2002
DOI: 10.3310/hta6290
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of established osteoporosis: a systematic review and cost-utility analysis

Abstract: Non-UK purchasers will have to pay a small fee for post and packing. For European countries the cost is £2 per monograph and for the rest of the world £3 per monograph.You can order HTA monographs from our Despatch Agents:-fax (with credit card or official purchase order) -post (with credit card or official purchase order or cheque) -phone during office hours (credit card only).Additionally the HTA website allows you either to pay securely by credit card or to print out your order and then post or fax it. Con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
93
0
2

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 207 publications
(100 citation statements)
references
References 172 publications
(487 reference statements)
4
93
0
2
Order By: Relevance
“…To date, the efficacy and cost-effectiveness of osteoporosis treatments, such as alendronate, have been studied extensively. (8)(9)(10)(11) However, it is less clear whether postmenopausal women with osteopenia should be treated with pharmaceuticals. One study from Europe showed that the cost-effectiveness of alendronate in osteopenic women without a history of fracture varies depending on the setting of each country, discount rate, and willingness to pay thresholds.…”
Section: Introductionmentioning
confidence: 99%
“…To date, the efficacy and cost-effectiveness of osteoporosis treatments, such as alendronate, have been studied extensively. (8)(9)(10)(11) However, it is less clear whether postmenopausal women with osteopenia should be treated with pharmaceuticals. One study from Europe showed that the cost-effectiveness of alendronate in osteopenic women without a history of fracture varies depending on the setting of each country, discount rate, and willingness to pay thresholds.…”
Section: Introductionmentioning
confidence: 99%
“…In line with a recent meta-analysis of the effects of bisphosphonates in post-menopausal osteoporosis [144] a relative risk reduction of treatment of 35% was assumed. A five-year intervention was assumed, which was chosen to approximate the time period for which there is direct or indirect clinical data on intervention effects.…”
Section: Study Objective and Analysis Frameworkmentioning
confidence: 99%
“…However, durations of three and ten years were also tested in sensitivity analyses. After stopping treatment, the risk reduction was assumed to reverse in a linear manner (also called the offset time of treatment effect) over a five-year period [118,144,145] in the base case.…”
Section: Study Objective and Analysis Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…Taking into account that the incidence of osteoporosis is 30-40% [5], the number of persons with osteoporosis in Serbia is 505 000 to 674.000. Having in mind that the risk of osteoporotic fractures is 10% [6], it could be estimated that 3500 to 5500 fractures may occur in Serbia annually.…”
Section: Introductionmentioning
confidence: 99%